The Principal's Democratic Leadership Style in Improving Teacher's Pedagogical Competence at SMPIT Auladina Indonesia, Bandar Lampung City - Cipto Handoko; An An Andari; Iskandar Zulkarnain; Sri Lestari (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The democratic leadership style of the principal of SMPIT Auladian Indonesia in Bandar Lampung City, in improving teacher pedagogic competence, namely decisions are made jointly between subordinates and leaders, respecting every potential possessed by subordinates, listening to criticism, suggestions/opinions from subordinates, collaborating with subordinates. To be able to assess the democratic leadership style of the madrasah principal, it can be seen from how many teachers have implemented pedagogical competence at SMPIT Auladina Indonesia, Bandar Lampung City. This study aims to determine the democratic leadership style of the principal in improving the pedagogic competence of teachers. This research method is a qualitative method which aims to find out a systematic, factual and accurate description of the facts in the field. To collect the necessary data, the authors use several methods, namely, interviews, observation, documentation. The subjects are the principal, and the teacher. Then analyzed using data analysis which consists of stages of data reduction, data presentation, and drawing conclusions. The conclusion of this study is that with the democratic leadership style of the principal in making decisions, the principal has made decisions by jointly making decisions by all parties involved from the teachers, and staff, then the principal way of appreciating every potential possessed by the teacher is by encouraging and supporting every activity made by the teacher, in listening to criticism, suggestions / opinions the principal always listens so that teachers and staff at SMPIT Auladina Indonesia, Bandar Lampung city are not awkward in talking with the madrasa principal. Principal also cooperate well with teachers and staff through cleaning activities.